Two-component gap solitons with linear interconversion - Adhikari, Sadhan K. [UNESP]; Malomed, Boris A. (American Physical Society (APS), 2009)
We consider one-dimensional solitons in a binary Bose-Einstein condensate with linear coupling between the components, trapped in an optical-lattice potential. The inter- and intraspecies interactions may be either repulsive or attractive. The main effects considered here are spontaneous breaking of the symmetry between components in symmetric and antisymmetric solitons, and spatial splitting between the components. These effects are studied by means of a variational approximation and numerical simulations. © 2009 The American Physical Society.